In whom do we trust? Critical success factors impacting intercultural communication in multicultural project teams - Yu, Wenyuan; Cormican, Kathryn; Wu, Qiong; Sampaio, Suzana (International Journal of Information Systems and Project Management, 2021)
Trust is a significant enabler for intercultural communication in project teams. Researchers and practitioners, therefore, need to know which factors might enhance trust in intercultural communication. Contributing to the yet limited number of studies in the field of intercultural communication for multicultural project teams, this research theoretically analyzes and empirically investigates the enablers of trust for intercultural communication focusing on emotional intelligence, empathy, interaction, and transparency. Using a field sample of 117 experienced project managers working in multicultural project teams, we find that interaction and transparency significantly and positively influence trust in intercultural communication; empathy marginally and positively influences trust. Emotional intelligence does not exert an effect on it. These results provide novel theoretical and empirical insights which have practical implications for project managers. The findings direct suggestions for additional theoretical work.